Development capabilities for smart products. Issue 2 (2019) - Tomiyama, Tetsuo; Lutters, Eric; Stark, Rainer; Abramovici, Michael
Abstract: Smart products supported by new step-changing technologies, such as Internet of Things and artificial intelligence, are now emerging in the market. Smart products are cyber physical systems with services through Internet connection. For example, smart vehicles equipped with advanced embedded intelligence are connected to other vehicles, people, and environment, and offer innovative data-driven services. Since smart products are software-intensive, data-driven, and service-conscious, their development clearly needs new capabilities underpinned by advanced tools, methods, and models. This paper reviews the status and trends of these emerging development technologies such as model-based systems engineering and digital twin.